The Experience of Adults with Multimorbidity: A Qualitative Study. Issue 1 (2014) - Duguay, Cynthia; Gallagher, Frances; Fortin, Martin
Background: Findings from several countries indicate that the prevalence of multimorbidity is very high among clients of primary healthcare. A deeper understanding of patients' experiences from their own perspective can greatly enrich any intervention to help them live as well as possible with multimorbidity. Objective: To describe the fundamental structure of adults' experience with multimorbidity. Design: A phenomenological study was undertaken to describe the experiences of 11 adults with multimorbidity. These adults participated in two semi-structured interviews, the content of which was rigorously analyzed. Results: At the core of the study participants' multimorbidity experience are the impression of aging prematurely, difficulties with self-care management, and issues with access to the healthcare system, which contribute to the problem's complexity. Despite these issues, participants with multimorbidity report attempting to take control of their situation and adjusting to daily living. Conclusions: The description of this experience, through the systemic vision of participants, provides a better understanding of the realities experienced by people with multimorbidity.